PERTANGGUNGJAWABAN PIDANA TERHADAP PENGEMBANG ARTIFICIAL INTELLIGENCE PADA KASUS PELANGGARAN PRIVASI DAN DATA PRIBADI - Musa Darwin Pane; Moch Zein Surya Permana (Cattleya Darmaya Fortuna, 2025)
The development of Artificial Intelligence (AI) technology has had a significant impact on various aspects of life, including the management of personal data. However, this progress also poses a risk of privacy violations and misuse of personal data by AI systems. This study aims to analyse criminal liability for AI developers in cases of privacy and personal data violations, focusing on applicable legal provisions and enforcement mechanisms. The research method used is normative juridical, by reviewing laws and regulations, court decisions, and related literature. The results showed that although the Personal Data Protection Act (UU PDP) and the Criminal Code (KUHP) have regulated the protection of personal data, there is a legal vacuum regarding the criminal liability of AI developers, especially when AI systems operate autonomously. This study recommends the need for specific regulations governing the responsibility of AI developers, including clear evidentiary mechanisms and sanctions, to ensure effective legal protection of privacy and personal data in the digital age.